Entrepreneurial process and performance: the case of the Turkish female entrepreneurs in Amsterdam - Tuzin Baycan Levent; Enno Masurel; Peter Nijkamp (European Regional Science Association (ERSA), 2002)
Ethnic entrepreneurship has become a popular concept in the modern multi-cultural society; in a modern 'multi-color' city ethnic entrepreneurship tends to become an indigenous and significant part of the local economy. This concept refers to business activities undertaken by entrepreneurs with a distinct socio-cultural or ethnic background. Ethnic groups often have a backward position in society, because of difficulties with native behavior, language and diploma's attitudes. The participation rate of ethnic groups in the urban labor market stays often behind and, when they do participate, they are often situated within the secondary labor market segments. For ethnic groups who are unable to adapt to a new social system, their marginal social position is a driving force to become self-employed some special talents. One way for migrants to escape from their backward position is to become an entrepreneur. In this case, self-employment is not only a means for earning a living, it is also a way of obtaining recognition and social acceptance. On the other hand, in the last few decades the participation rate of women in the labour market has increased in most Western countries. An increase in the participation rate of women does not necessarily imply an increase in the number of female entrepreneurs. However, it does increase the likelihood of women to become self-employed. Moreover, women contribute to the diversity in the supply of entrepreneurship, because they may have a different approach towards entrepreneurship compared to men. Despite the scarcity of data, recent observations show the involvement of women in entrepreneurial activity and self-employment rates, which include women who own and operate their own businesses are increasing around the world. According to available data, between one-quarter and one-third of the formal sector businesses are owned and operated by women. The aim of this paper is to describe and understand the entrepreneurial processes of ethnic females. In which way and to which extent are these processes the result of: a) unemployment b) job level c) poor performance in terms of wages d) work experience e) educational level f) language g) discrimination h) socio-cultural and ethnic networks? Or in other words, what are the factors that stimulate females to find other income generating activities? What are the important factors for the motivation and performance of female entrepreneurship? Which factors contribute to the success or failure of ethnic female entrepreneurs? And how do these female entrepreneurs experience failure or survival? What is the satisfaction level of female entrepreneurs? This study aims to provide an answer to these questions on the basis of case study research on Turkish female entrepreneurs in Amsterdam.
Keywords: 330